The Influence of Islamic Financial Literacy on Sharia Digital Finance for Consumers at Pegadaian Syariah Gorontalo - Cahyati, Cici; Niswatin, Niswatin; Hiola, Yustina (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2025)
Indonesia, as a nation characterized by a Muslim-majority population, plays an important contribution to the advancement of Islamic finance, especially in line with digitalization advancements. This condition has driven the growth of various sharia-based digital businesses, including online platforms and fintech that implement sharia-compliant transaction principles. Islamic financial literacy describes a person's knowledge and comprehension of financial products and services that comply with Islamic principles, as well as their capacity to differentiate between conventional and Islamic banking systems. A prevailing issue is that sharia financial literacy remains low, despite showing annual growth. This research seeks to analyze the impact of Islamic financial literacy on digital sharia finance services at Pegadaian Syariah Gorontalo. The research applies A quantitative method utilizing purposive sampling technique method, involving 94 respondents. A simple linear regression method was employed to analyze the data through SPSS version 30. The findings show that Islamic financial literacy has a significant impact influences digital sharia finance.